2017
DOI: 10.1002/pi.5344
|View full text |Cite
|
Sign up to set email alerts
|

Coarse‐grained models for frontal photopolymerization with evolving conversion profile

Abstract: We introduce a series of ‘minimal’ models to describe a common light-driven directional solidification process, known as frontal photopolymerization (FPP), focusing on experimental observables: the solidification kinetics, light attenuation and spatiotemporal monomer-to-polymer conversion. Specifically, we focus on FPP propagation that yields conversion profiles that are not invariant with time, and which cannot be simply described by the presence of mass or heat diffusion. The models are assessed against expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…29 This effect, known as frontal photopolymerization (FPP) or photofrontal polymerization, 30 creates a front of polymerization that propagates within the sample during irradiation. 28,31 Different authors have proposed some models to account for the frontal polymerization 29,[32][33][34][35] and it has been concluded that if the photoinitiator bleaches, the front propagates at a constant velocity in the sample. 36 This has been used to generate gradient optical materials 37,38 or microfluidic devices.…”
Section: Resultsmentioning
confidence: 99%
“…29 This effect, known as frontal photopolymerization (FPP) or photofrontal polymerization, 30 creates a front of polymerization that propagates within the sample during irradiation. 28,31 Different authors have proposed some models to account for the frontal polymerization 29,[32][33][34][35] and it has been concluded that if the photoinitiator bleaches, the front propagates at a constant velocity in the sample. 36 This has been used to generate gradient optical materials 37,38 or microfluidic devices.…”
Section: Resultsmentioning
confidence: 99%
“…A novel model of FPP, incorporating mass transport and the mechanical response of the polymer network, was found to describe all experimental data obtained using a commercial thiol-ene formulation (NOA81). By accounting for heat generation and transport 36 or multiple reaction steps, 72 the applicability of the model can be extended to a range of noncommercial thiol-ene and acrylate systems, as previously demonstrated. 27 Significantly, the model yields an estimate of the time at which swelling is relevant, and is found to agree with experiments.…”
Section: Discussionmentioning
confidence: 97%
“…where K is an effective rate coefficient for the conversion process. A more precise description of K in terms of detailed chemical reactions can be found in Purnama et al 72 The intensity of light is modelled using a Beer-Lambert law…”
Section: Model Formulationmentioning
confidence: 99%